Identification of quantitative trait loci, candidate genes and diagnostic markers for Hessian fly resistance in wheat - Xu, Xiaoting (Kansas State University, 2024)
Hessian fly (HF), Mayetiola destructor (Say), is a destructive insect pest of wheat (Triticum aestivum L.) worldwide. Growing resistant cultivars is the most effective approach for HF management. Although over 50 HF resistance (H) genes and quantitative trait loci (QTL) have been reported, only a few of them have been deployed in limited areas due to their loss of effectiveness against predominant HF biotypes, and lack of diagnostic markers for breeding selection. To discover new resistant sources, screening Pakistani wheat landraces and cultivars identified a highly HF resistant wheat cultivar ‘Parvaz-94’. Two QTL (QHf.hwwg-1AS.2 and QHf.hwwg-6BS.2) were mapped using a high-density linkage map of single nucleotide polymorphisms (SNPs) developed from recombinant inbred lines (RILs) of Parvaz-94 x Cadenza. QHf.hwwg-1AS.2 and QHf.hwwg-6BS.2 were mapped to a 4.0 Mb interval (4.6–8.6 Mb) on 1AS and a 5.4 Mb interval (2.3–7.7 Mb) on 6BS, respectively, based on IWGSC RefSeq v2.1 reference. QHf.hwwg-6BS.2 alone conferred complete HF resistance, whereas QHf.hwwg-1AS.2 showed partial resistance. To facilitate cloning of H35 on 3BS that was previously identified in the U.S. winter wheat cultivar ‘Overland’, a 14.57 Gb assembly of Overland (Overland v1.1) was generated using PacBio high-fidelity (HiFi) long reads. Screening of over 8,000 plants with the flanking markers identified 36 critical new recombinants in the H35 interval. With 12 newly developed kompetitive allele specific PCR (KASP) markers, H35 interval was finely mapped to a 38 kb interval in Chinese Spring (IWGSC RefSeq v2.1) and around 70 kb interval in Overland (v1.1), with only three and four putative genes, respectively, in the interval. Two of the genes significantly differentially expressed between two H35 near iso-genetic lines using RNA-sequencing and were selected as the candidates for further function validation. To facilitate marker-assisted breeding for HF resistance, we developed and validated breeder-friendly KASP markers for QHf.hwwg-6BS.2, H35 and H13. H13 on 6DS is a recently cloned resistance gene that originated from Aegilops tauschii; however, selectable markers were not available. In this study, KASP marker K6B_7697506 tightly linked to QHf.hwwg-6BS.2 was developed and validated in three U.S. winter wheat diversity panels; KB120-2, a near diagnostic marker for H35, was validated in the AM203 panel and showed best performance in RGON2022 among four markers derived from H35 candidate genes; H13-1a, converted from a nonsense mutation of H13, was validated in the AM203 panel and three soft winter wheat lines known to carry H13. These markers can be used for marker-assisted selection to facilitate quick deployment of these genes in U.S. wheat cultivars to enhance HF resistance level and durability in breeding programs.
Keywords: Mayetiola destructor; Triticum aestivum; QHf.hwwg-6BS.2; H35; H13; Kompetitive allele specific PCR marker